The impact of non-neurological organ dysfunction on outcomes in severe isolated traumatic brain injury. Issue 2 (August 2020) - Astarabadi, Mariam; Khurrum, Muhammad; Asmar, Samer; Bible, Letitia; Chehab, Mohamad; Castanon, Lourdes; Ditillo, Michael; Douglas, Molly; Joseph, Bellal
Abstract : INTRODUCTION: Organ dysfunction following traumatic brain injury (TBI) is common and has been associated with unpredictable outcomes. The aim of our study is to describe the incidence of non-neurological organ dysfunction (NNOD) and its impact on outcomes in patients with severe TBI admitted to our intensive care unit (ICU). METHODS: We performed a 3-year (2015-2017) review of our Level 1 trauma center's prospectively maintained TBI database and included all adult (age ≥18y) patients with isolated severe TBI (head abbreviated injury severity (AIS) ≥3 and other AIS <3) and an ICU stay >48 hours. Organ dysfunction (OD) was measured by multiple organ dysfunction scores. Organ system failure was defined as a non-neurological component score of ≥3 on any day during the ICU stay. Outcomes measured were the incidence of NNOD and its effect on outcomes. Multivariate regression analysis was performed. RESULTS: A total of 285 patients were included. The mean age was 48 ± 22 years, 72% were males, median [IQR] Glasgow Coma Scale (GCS) was 8[5-10], and median Injury Severity Score (ISS) was 17[10-26]. Epidural hematoma was the most common intracranial hemorrhage (49%) followed by subdural hematoma (46%). The overall incidence of NNOD was 33%, with the most common dysfunctional organ system being the respiratory (23%) followed by the cardiovascular (12%) and hepatic system (8%). The overall in-hospital mortality rate was 19% (NNOD:36% vs. No-NNOD:9%, p < 0.01). On regression analysis, NNOD was associated with higher in-hospital mortality (aOR: 2.0 [1.6-2.7]), discharge to skilled nursing facility (SNF) (aOR: 1.8 [1.4-2.2]), and Glasgow Outcome Scale-Extended (GOS-E) ⩽4 (OR: 1.7 [1.3-2.3]) and p -values <0.01. CONCLUSION: One in every three isolated severe TBI patients develop NNOD. NNOD is independently associated with worse outcomes. Understanding the mechanisms associated with NNOD in the setting of TBI may promote prevention practices and improve outcomes in TBI. LEVEL OF EVIDENCE: Prognostic, level III. Abstract : Supplemental digital content is available in the text.